Technology for Development: Ten True Stories Revealing the Complexity of Replicating South Korean Success - Nawaz M. Sharif (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2020)
This essay comprises ten true stories presented to highlight personally observed problematic encountered by Asian developing country leadership who tried to replicate South Korean success in fostering technology innovation induced sustainable economic growth strategy without paying robust attention to the crucial role of creating an